South American scientific research on the use of botulinum toxin in plastic surgery: a bibliometric analysis of articles indexed in Scopus - Fuentes-Zamudio, Oscar Darío (2024)
Objective: To analyze the scientific evolution of botulinum toxin usage in plastic surgery in Latin America. Materials and methods: A cross-sectional bibliometric study was conducted using Scopus as the data source. Visual and bibliometric analyses were performed, and metrics were generated to evaluate the evolution, general characteristics and impact of the Latin American evidence on the use of botulinum toxin in plastic surgery. The bibliometrix R-package was utilized for this analysis. Results: The study included 34 documents published between 2002 and 2023, out of which 70.5 % (n = 24) were original articles and 23.5 % (n = 8) were reviews. International collaboration was identified in 32.3 % of the cases. The four most prolific authors were from Colombia and Brazil, each having published only two documents. Brazil (n = 20) was the most prolific country, followed by Chile (n = 5), Argentina (n = 4) and Colombia (n = 4). Regarding research trends, it was found that quality of life, dermal fillers, hyaluronic acid and wrinkles were the subtopics most related to the use of botulinum toxin in plastic surgery in Latin America. There were basically five associated research lines related to symptoms and aesthetic procedures, cosmetic complications and quality of life. The degree of development of the topics essentially depended on aesthetic interventions. Multiple correspondence analysis based on authors’ keywords revealed that patient follow-up, cohort studies, risk assessment, outcome evaluation, rejuvenation and adults are elements that primarily complement the base subtopics. Conclusions: Slow growth with low production and impact has been identified in Latin American research on the use of botulinum toxin in plastic surgery over the last 20 years. This research has focused on clinical studies related to clinical outcome assessment, quality of life and aesthetic techniques. Brazil leads research in the region and maintains a strong network of intercontinental collaboration.